2020
DOI: 10.1080/13607863.2020.1839863
|View full text |Cite
|
Sign up to set email alerts
|

Digital technology use and depressive symptoms among older adults in Korea: beneficial for those who have fewer social interactions?

Abstract: Objectives: Our study examines the relationship between digital technology use and depressive symptoms among older Koreans and whether social interaction moderates the relationship. Methods: The data were drawn from the 2017 Survey of Living Conditions and Welfare Needs of Korean Older Persons, a nationally representative survey. Digital technology use was measured by the number of digital functions that respondents perform with their electronic devices. Social interactions were measured by the frequencies of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 28 publications
6
46
0
Order By: Relevance
“…This result is in line with other findings suggesting that in-person communication is crucial for mental health in older adults, particularly for those who live alone (Fingerman et al, 2021). A related study showed that the use of digital communication was more beneficial for the mental health of older adults who used it infrequently than for those who used it frequently (Lee et al, 2020). Furthermore, another study found that the probability of having depressive symptoms steadily increased with age in older adults as the frequency of in-person, but not phone, written or e-mail contact, decreased (Teo et al, 2015).…”
Section: Discussionsupporting
confidence: 91%
“…This result is in line with other findings suggesting that in-person communication is crucial for mental health in older adults, particularly for those who live alone (Fingerman et al, 2021). A related study showed that the use of digital communication was more beneficial for the mental health of older adults who used it infrequently than for those who used it frequently (Lee et al, 2020). Furthermore, another study found that the probability of having depressive symptoms steadily increased with age in older adults as the frequency of in-person, but not phone, written or e-mail contact, decreased (Teo et al, 2015).…”
Section: Discussionsupporting
confidence: 91%
“…This may be a means by which participants who engaged in such activity were able to prevent even higher levels of loneliness during social distancing, and in some cases were able to experience lower levels of loneliness. Thus, educating older adults to increase their digital literacy level and use of remote social interactions could be a really important tool for addressing issues such as loneliness [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although the event-contingent design has several advantages for our study, it is also prone to different kind of biases (e.g., related to memory, self-awareness, or self-presentational concerns). Previous research has shown that digital technology use is more beneficial for older adults with infrequent contact with friends or neighbors than for those with frequent contact (Lee et al, 2020). Our study is based on a volunteer sample recruited from advertisements and participant database at the university.…”
Section: Discussionmentioning
confidence: 99%
“…In cross-sectional data from a nationally representative sample of Korean older adults, higher numbers of digital activities were associated with lower levels of depressive symptoms. In addition, the association between digital technology use and depressive symptoms was stronger in older adults who reported less frequent remote contact with their social circle, suggesting that those more at risk of social isolation might benefit more from using digital technology (Lee et al, 2020). In sum, these findings suggest that the use of digital communication technologies may increase social connectedness and well-being in older adults, especially in those who may lack social interaction otherwise.…”
mentioning
confidence: 99%